Pemanfaatan Limbah Budidaya Ikan Lele Dengan Sistem Akuaponik Di Kelurahan Gedog - Yessy Risma Priranti; Rizky Ramadhani; Aldia Safira Hartono; Nabila Zafirna Syazwani; Aprilia Retnowati; Dewi Puspa Arum (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The Women Farmers Group (KWT) “Guyub Rukun” in Gedog Village has the potential to produce vegetables using an aquaponics system. This is supported by the large amount of waste from catfish farming. Utilization of catfish farming waste is still not optimal. The use of catfish farming waste from the Women Farmers Group (KWT) "Guyub Rukun" RW 13 has not resulted in vegetable production through the aquaponics system. The empowerment activities of the Women Farmers Group (KWT) "Guyub Rukun" RW 13 aim to provide information, training and assistance on how to use catfish farming waste through an aquaponic system to produce agricultural products in the form of vegetable crops and reduce pollution resulting from catfish farming waste. This activity received a positive response from the Women Farmers Group (KWT) "Guyub Rukun" RW 13. From the results of this empowerment activity, the Women Farmers Group (KWT) "Guyub Rukun" RW 13 understood and were able to utilize catfish farming waste.